A new species of Trichomyia Haliday (Diptera: Psychodidae: Trichomyiinae) from the Brazilian Atlantic Forest, with a checklist of Western Hemisphere species - Santos, Claudiney Biral Dos; Leite, Gustavo Rocha (Zootaxa, 2012)
Trichomyia pintoi sp. nov. is described and illustrated from male specimens collected from the Atlantic Forest, southeastern Brazil. T. pintoi is grouped with the globally distributed Trichomyia that have 3 palpus segments. It is easily distinguished by the 8 strong spines inserted in the distal third of the gonocoxite. A checklist of described Western Hemisphere Trichomyia species is provided.